PRESENTASI INTERAKTIF DALAM PEMBELAJARAN DARING - Desirizta Sari Steviani (Ekasakti Jurnal Penelitian dan Pengabdian, 2020)
Online learning or known as online learning is part of e-learnings. In doing online learning,interactive presentations are needed. Interactive presentations can be created by involvingEducation and Training participants as well as two-way communication between theFacilitator and participants. To realize interactive presentations in online learning must besupported bya variety of learning methods using a variety of available applications. Themethods that can be used for interactive presentations in online learning are lectures,question and answer, discussion, brainstorming and evaluation methods. This methodbecomesinteresting when supported by using the Collud Meeting Zoom, Slido, Jamboard,Padlet and Quizizz applications.